The Role of Parents Based on Their Type of Work: How to Motivate Children's Learning - Abimanyu, Moh Anggita; Ismaya, Erik Aditia; Setiawan, Deka (Papanda Publisher, 2023)
The role of parents is pivotal in shaping a child's educational journey, particularly in motivating their learning. This research aims to explore how parental occupations influence their roles in motivating their children's learning, focusing on Honggosoco Village. Employing qualitative methods, data were collected from five families, revealing significant impacts of parental occupations on their roles in educating their children. Parents with flexible work schedules tend to be more effective in providing encouragement, guidance, and appreciation to their children. Conversely, parents with demanding work schedules face limitations in time and energy, affecting their ability to support their children adequately. This study underscores how parental roles in children's education are influenced by their occupational choices, consequently influencing children's learning motivation. The findings highlight the importance of parental understanding and awareness of their roles in their children's education. Training programs for parents are recommended to enhance their skills and knowledge in supporting their children's education. Empowering parents is acknowledged as a solution to enhance children's motivation and academic achievements. Thus, enhancing parental involvement in education can significantly contribute to the positive development of children's education in Honggosoco Village and potentially in other regions.